2014
DOI: 10.1186/2191-219x-4-16
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and radiodosimetry of a novel myocardial perfusion tracer 123I-CMICE-013 in healthy rats

Abstract: Background123I-CMICE-013 is a novel radiotracer previously reported to have promising characteristics for single-photon emission computed tomography (SPECT) myocardial perfusion imaging. We evaluated the biokinetics and radiodosimetry of this rotenone-like 123I-labeled tracer in a microSPECT imaging-based study.Methods37 to 111 MBq of 123I-CMICE-013 was synthesized and administered intravenously to 14 healthy rats. Images were acquired with a microSPECT/CT camera at various time intervals and reconstructed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Statistical analysis of the correlation between data acquired by in vivo SPECT and ex vivo biodistribution was evaluated with linear regression analysis and a Pearson correlation coefficient (r) using the SciPy package in Python (Finucane et al 2011, Duan et al 2014, Virtanen et al 2020. Statistical significance was set as p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis of the correlation between data acquired by in vivo SPECT and ex vivo biodistribution was evaluated with linear regression analysis and a Pearson correlation coefficient (r) using the SciPy package in Python (Finucane et al 2011, Duan et al 2014, Virtanen et al 2020. Statistical significance was set as p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…CMICE-013 has a good toxicity profile (8), and initial biodistribution studies in rats demonstrated excellent uptake in the heart and contrast with surrounding organs. The effective dose of a 185-MBq injection was estimated from preclinical studies to be 1.3-3.9 mSv (9,10). This study's objectives were to assess the image quality of CMICE-013 and compare its uptake with tetrofosmin, sestamibi, and 201 Tl in vivo in a porcine model of myocardial ischemia.…”
mentioning
confidence: 99%